Premature Ventricular Complexes: Diagnose, Evaluation, and Management - Handayani, Ahmad; Lubis, Anggia Chairuddin (Buletin Farmatera, 2022)
Premature ventricular complexes (PVCs) are arrhythmias due to abnormal impulse formation in the ventricles. The incidence is detected as much as 1% on standard electrocardiographic (ECG) examination. The aim of this literature review is to explain the diagnosis, evaluation, and management of PVC. The diagnosis of PVC is determined from the symptoms and evidence from the ECG recording. Symptoms may include a faster heartbeat sensation, chest discomfort, skipped beat, and intermittenly strong heartbeat. Evidence of PVC is established by regular ECG recordings or Holter. A 12-ECG can help determine the location of source. PVC evaluation includes determine the dangerousity, the next examination step, the treatment options, and whether ablation is needed. Managements include medical therapy and catheter ablation. Catheter ablation is performed where treatment is unsatisfactory or if the PVC causing life threathening arrhythmia or cardiomyopathy. PVC is considered dangerous if the underlying disease is found in the form of cardiac structural abnormalities, ischemic heart disease or other arrhythmic disorders, more than 2000 PVC is found in 24 hours, complex morphology, different morphology, increased with exercise, PVC with non-outflow tract form, with short coupling interval, and with a wider QRS duration The incidence of VVC that is considered to be able to induce cardiomyopathy is from 10-26%. PVC requires a structured and systematic diagnosis and evaluation step to determine the appropriate treatment.